SMU and RHT Rajan Menon Foundation affirm commitment to cultivate pro bono spirit among law students and within the legal fraternity - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
In conjunction with the official launch of the Singapore Management University (SMU) Pro Bono Centre’s new premises at the SMU School of Law building today, the University announced a gift of S$300,000 from the RHT Rajan Menon Foundation, which will support the Centre for a period of five years starting from Academic Year 2017-2018. Both parties are also delighted to announce the appointment of Mr Chan Sek Keong, former Chief Justice and current Senior Judge of the Singapore Supreme Court as the Centre’s Advisor. Mr Chan unveiled the new premises today at the launch ceremony today, together with SMU Provost, Professor Lily Kong, and Mr Tan Chong Huat, Chairman of RHT Rajan Menon Foundation.